Autonomic, hormonal, and subjective responses to a modified version of the TSST: a pilot study - Espín López, Laura; Salvador, Alicia; Gómez-Amor, Jesús (Anales de Psicología / Annals of Psychology, 2021)
The aim of this research was to study hormonal, autonomic and affective responses to a modified version of the stressor TSST in a sample of young university students composed for thirty-eight subjects (11 men and twenty seven women, 11 in the luteal phase of the menstrual cycle, 16 women in the follicular phase). The hormonal response was evaluated with levels of cortisol. Heart rate and Electrodermal Activity were recorded during all the experimental session and trait-state anxiety was evaluated before and after the task. The speech phase elicited the highest heart rate, frequency of non-specific response and skin conductance level, showing significant differences mainly with the habituation phase. However, the salivary cortisol response was not significant with respect to stressor. In relation with sex differences, regardless of the stressor, menshowed higher frequency of non-specific response, greater skin conductance level than women and higher cortisol levels in comparison with women in the luteal phase. State-anxiety was similar pre-/post task and did not reveal any difference associated to sex or menstrual cycle phase. Our results suggest that the HPA axis not response to sitting TSST and provided evidence that TSST elicits different pattern of psychophysiological response depending on some protocol variations.